GPCRs of adrenal chromaffin cells & catecholamines: The plot thickens. (August 2016) - Lymperopoulos, Anastasios; Brill, Ava; McCrink, Katie A.
Abstract: The circulating catecholamines (CAs) epinephrine (Epi) and norepinephrine (NE) derive from two major sources in the whole organism: the sympathetic nerve endings, which release NE on effector organs, and the chromaffin cells of the adrenal medulla, which are cells that synthesize, store and release Epi (mainly) and NE. All of the Epi in the body and a significant amount of circulating NE derive from the adrenal medulla. The secretion of CAs from adrenal chromaffin cells is regulated in a complex way by a variety of membrane receptors, the vast majority of which are G protein-coupled receptors (GPCRs), including adrenergic receptors (ARs), which act as "presynaptic autoreceptors" in this regard. There is a plethora of CA-secretagogue signals acting on these receptors but some of them, most notably the α2 ARs, inhibit CA secretion. Over the past few years, however, a few new proteins present in chromaffin cells have been uncovered to participate in CA secretion regulation. Most prominent among these are GRK2 and β-arrestin1, which are known to interact with GPCRs regulating receptor signaling and function. The present review will discuss the molecular and signaling mechanisms by which adrenal chromaffin cell-residing GPCRs and their regulatory proteins modulate CA synthesis and secretion. Particular emphasis will be given to the newly discovered roles of GRK2 and β-arrestins in these processes and particular points of focus for future research will be highlighted, as well.